Analysis of emotion using skin conductance in music listening / Asma' Ismail - Ismail, Asma' (2013)
Physiological signals for emotion is very well known among physiologists. It is being explored in order to recognize the people's emotion. However, little attention has been paid so far to this matter compared to audio-visual emotion channels such as speech or facial expression. Therefore, the purpose of this study is to analyze the user's emotion by adopting physiological measurement. There are three key findings that have been discovered including types of emotions, number of peaks, and pattern of graph. For collecting physiological signals, four songs have been chosen and skin conductance is used as physiological measurement. The skin conductance is measured by attaching the device to the participants's fingers and the graphs will be produced. From the results, it shows that the main types of emotions have been produced while listening to all types of song such as happy, anger, stressful, sad, calm, and relax. These results are based on questionnaires given. Besides that, the graph of skin conductance also shows the number of peaks and graph pattern among participants. As a result, the findings of this study provide empirical evidence that physiological measurement able to detect one's emotion and the findings also can be used for further research in the future.